Virologic and immunologic response to cART by HIV-1 subtype in the CASCADE collaboration. - Giota Touloumi; Nikos Pantazis; Marie-Laure Chaix; Heiner C Bucher; Robert Zangerle; Anne-Marte Bakken Kran; Rodolphe Thiebaut; Bernard Masquelier; Claudia Kucherer; Antonella d'Arminio Monforte; Laurence Meyer; Kholoud Porter; et al. (PLoS ONE, 2013)
We aimed to compare rates of virologic response and CD4 changes after combination antiretroviral (cART) initiation in individuals infected with B and specific non-B HIV subtypes.Using CASCADE data we analyzed HIV-RNA and CD4 counts for persons infected ≥1996, ≥15 years of age. We used survival and longitudinal modeling to estimate probabilities of virologic response (confirmed HIV-RNA <500 c/ml), and failure (HIV-RNA>500 c/ml at 6 months or ≥1000 c/ml following response) and CD4 increase after cART initiation.2003 (1706 B, 142 CRF02_AG, 55 A, 53 C, 47 CRF01_AE) seroconverters were included in analysis. There was no evidence of subtype effect overall for response or failure (p = 0.075 and 0.317, respectively) although there was a suggestion that those infected with subtypes CRF01_AE and A responded sooner than those with subtype B infection [HR (95% CI):1.37 (1.01-1.86) and 1.29 (0.96-1.72), respectively]. Rates of CD4 increase were similar in all subtypes except subtype A, which tended to have lower initial, but faster long-term, increases.Virologic and immunologic response to cART was similar across all studied subtypes but statistical power was limited by the rarity of some non-B subtypes. Current antiretroviral agents seem to have similar efficacy in subtype B and most widely encountered non-B infections in high-income countries.